2006
DOI: 10.1197/j.aem.2005.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐based Morbidity and Mortality Conference: New Technologies Augmenting Traditional Case‐based Presentations

Abstract: The authors describe the use of a high-fidelity simulation laboratory to re-create a patient encounter for the purposes of enhancing a morbidity and mortality conference. The use of two separate technologies were enlisted: a METI high-fidelity patient simulator to re-create the case in a more lifelike fashion, and an audience response system to collect clinical impressions throughout the case presentation and survey data at the end of the presentation. The re-creation of the patient encounter with all relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Simulation scenarios with two or more simultaneous patients are being used to develop multitasking, crew resource management, and decision‐making skills without risk to actual patients 53 . High‐fidelity simulation has even been used to replicate patient encounters during morbidity and mortality conferences 54 . Internationally, simulation has been used to challenge the traditional techniques of medical education on an even larger scale.…”
Section: Simulation‐based Teaching In Gmementioning
confidence: 99%
See 1 more Smart Citation
“…Simulation scenarios with two or more simultaneous patients are being used to develop multitasking, crew resource management, and decision‐making skills without risk to actual patients 53 . High‐fidelity simulation has even been used to replicate patient encounters during morbidity and mortality conferences 54 . Internationally, simulation has been used to challenge the traditional techniques of medical education on an even larger scale.…”
Section: Simulation‐based Teaching In Gmementioning
confidence: 99%
“…Doing scenarios in nontraditional locations, such as the back of an ambulance or in a medical helicopter, 96 may also be highly effective. Large groups can experience and benefit from simulation in a lecture hall setting with some creative modifications to cases and presentation formats in both live 18 and prerecorded 54 simulation scenarios.…”
Section: Developing a Simulation Centermentioning
confidence: 99%
“…Pausing the scenario allowed key points to be brought out for discussion. It was also felt that it removed some of the artificiality associated with case‐based discussions and allowed teamwork behaviours to be observed and discussed 41 …”
Section: The Role Of Mannequin‐based Simulation In Emergency Medicinementioning
confidence: 99%
“…Furthermore, national patient safety organisations have themselves described essential patient safety competencies, many of which are reinforced through the use of M&M rounds 4. Some authors have also suggested that M&M rounds should be an essential component of the learner curriculum 5 6. At our own institution, residents present 100% of surgical M&M rounds and 23% of non-surgical M&M rounds (personal correspondence with Dr Lisa Calder and Mr Craig MacKie).…”
Section: Introductionmentioning
confidence: 97%